Translation and Validation of the AttrakDiff User Experience Questionnaire to Spanish - López Herrera, Gustavo (2023)
The AttrakDiff questionnaire is a widely used instrument for measuring User Experience. However, a Spanish version of the questionnaire has yet to be validated. This represents a significant limitation, given the importance of the Spanish-speaking community. This study aims to translate and validate AttrakDiff to Spanish. Several techniques for translation were used, and the results were joined in a translation proposal. The translated version was evaluated in two scenarios. First, an evaluation with 200 + participants to assess the translation proposal. Second, an evaluation of three systems to perform a factorial analysis and determine the correlations between questions of the same dimension. The results of this study will contribute to the advancement of UX research and practice in the Spanish-speaking context and provide a valuable tool for practitioners and researchers who work with Spanish-speaking users.